2011
DOI: 10.1634/theoncologist.2011-0105
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Early Alpha-Fetoprotein Level Changes in Predicting Clinical and Survival Benefits in Advanced Hepatocellular Carcinoma Patients Receiving Sorafenib

Abstract: Background. The role of serum alpha-fetoprotein (AFP) changes in predicting the treatment outcomes of advanced hepatocellular carcinoma (HCC) patients to sorafenib remains unknown.Methods. Serum AFP was collected prospectively at baseline and subsequent follow-up visits in parallel with clinical and survival outcomes. AFP response was defined as a relative drop of AFP >20% of the baseline level after 6 weeks of sorafenib. The relationship between AFP response and the treatment outcomes was first explored in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 17 publications
4
65
2
2
Order By: Relevance
“…Small series reported the value of baseline and changes in AFP plasma levels to predict response and outcome for patients with advanced HCC treated with sorafenib. Several studies showed consistent correlation between early (varying from 2 to 8 wk) decrease of AFP level more than 20% following sorafenib and objective response [69][70][71][72][73] and better outcome [69][70][71]73] in patients with advanced HCC. Personeni et al [71] showed that early responders, defined by a 20% decrease of AFP 8 wk after sorafenib treatment, had significantly better median OS and TTP compared to non-responders (13.8 mo vs 8.2 mo, P = 0.022 and 7.9 mo vs 2.4 mo, P = 0.004; respectively) [71] .…”
Section: Poorer Prognosismentioning
confidence: 83%
See 1 more Smart Citation
“…Small series reported the value of baseline and changes in AFP plasma levels to predict response and outcome for patients with advanced HCC treated with sorafenib. Several studies showed consistent correlation between early (varying from 2 to 8 wk) decrease of AFP level more than 20% following sorafenib and objective response [69][70][71][72][73] and better outcome [69][70][71]73] in patients with advanced HCC. Personeni et al [71] showed that early responders, defined by a 20% decrease of AFP 8 wk after sorafenib treatment, had significantly better median OS and TTP compared to non-responders (13.8 mo vs 8.2 mo, P = 0.022 and 7.9 mo vs 2.4 mo, P = 0.004; respectively) [71] .…”
Section: Poorer Prognosismentioning
confidence: 83%
“…An inverse link between sVEGFR-2 plasma levels and tumor size was detected. Recently, sVEGFR-1 levels were shown to be associated with more advanced-stage HCC and tumor differentiation and sVEGFR-2 levels to be associated with [70] 94…”
Section: Poorer Dfs Higher Vascular Invasionmentioning
confidence: 99%
“…4). Early AFP response following the initiation of sorafenib therapy has previously been identified as a positive prognostic factor for patients with advanced HCC (15). Further investigation regarding the contributing factors and molecular pathophysiology of these sorafenib responders is required.…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, 2 focused on patients that were treated with sorafenib (4, 5), whereas a 3rd report considered metronomic chemotherapy in combination with various antiangiogenic agents, including sorafenib (3). Despite differing timings adopted for the appraisal of AFP response, results of these investigations indicate a substantial agreement in that they show that AFP responders experience longer time to progression (5), progression-free survival (3,4), and overall survival, compared with patients classified as AFP nonresponders.…”
mentioning
confidence: 92%
“…In this respect, we anticipate that, as opposed to the cohort studies mentioned above (3)(4)(5), the phase III SHARP trial (2) should provide the appropriate context in which to explore AFP response as a surrogate marker of outcome in HCC patients receiving sorafenib. …”
mentioning
confidence: 99%